Validation of a German version of the International Hip Outcome Tool 12 (iHOT12) according to the COSMIN checklist - Baumann, Florian; Fickert, Stefan (Health and quality of life outcomes, 2016)
Background: Patient Reported Outcome (PRO) measurements have become an important tool to evaluate disease-related quality of life. The “International Hip Outcome Tool” (iHOT12) is a self-administered patient-reported outcome tool, which includes questions on the patient’s symptoms, functional and sports limitations as well as social, emotional, and occupational limitations. The purpose of this study was to adapt and validate a German version of the iHOT12 according to the COSMIN checklist. Methods: In order to validate the German translation of the iHOT12, we conducted a prospective multicenter cohort study on patients with hip disorders and a score ≥4 on the modified Tegner Activity Scale (mTAS). The patients completed the German iHOT12 questionnaire and other functional scores (Hip Outcome Score, modified Tegner Activity Scale, EuroQol-5D) twice at intervals of at least two weeks. Evaluation of psychometric properties was conducted following the COSMIN checklist for validation of health status measurement instruments. The methodical testing for reliability included internal consistency, test-retest reliability, and measurement error. For testing of validity, we analyzed construct validity, hypotheses testing, interpretability and responsiveness. Results: Between December 2013 and December 2014, eighty-three consecutive patients completed both questionnaires and were available for data analysis. Cronbach’s alpha was 0.94 (95 %-CI: 0.91, 0.95) confirming internal consistency and test-retest reliability of the iHOT-12 was high with an ICC = 0.94 (95 %-CI: 0.89, 0.97). All a priori hypotheses were confirmed. Further, no relevant floor- or ceiling effects occurred. The iHOT12 showed good responsiveness with a minimal important change (MIC) under 14 points. Conclusions: The German translation of the iHOT-12 is a reliable, valid, and responsive tool for the evaluation of disease-related quality of life in active patients with a hip disorder. We could show that the minimal important change, a change of health condition the patient discerns, is less than 14 points in the iHOT12 scale.